Mineral stress response of Vitis cell wall transcriptome: identification, characterization and expression of genes from key families involved in wall biosynthesis and modification - Fernandes, João Carlos Martins (2016)
Doutoramento em Engenharia Agronómica - Instituto Superior de Agronomia - UL